2020
DOI: 10.1016/j.ssaho.2020.100061
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of quarantine period on asymptomatic individuals with COVID-19

Abstract: Background Coronavirus Disease is one of the most highly infectious diseases was reported worldwide as pandemic. This infectious virus transmits through several methods among individuals, for controlling this transmission most effective nonpharmacological strategy to controlling the infections is Quarantine the affected or suspected asymptomatic individuals. Aim To assess the psychological impact of quarantine period on asymptomatic individuals with COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
(23 reference statements)
2
13
0
Order By: Relevance
“…On the contrary, another study showed that subjects suspected with COVID-19 could experience psychological distress due to uncertainty over disease status. Separation from family and loneliness along with negative stigmatization also became other issues during the quarantine period which could worsen psychological health ( 72 , 73 ). Moreover, the majority of respondents in this research came from a higher education level.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, another study showed that subjects suspected with COVID-19 could experience psychological distress due to uncertainty over disease status. Separation from family and loneliness along with negative stigmatization also became other issues during the quarantine period which could worsen psychological health ( 72 , 73 ). Moreover, the majority of respondents in this research came from a higher education level.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was observed by Lee et al where no difference was observed for anxiety among individual under quarantine and without quarantine ( Lee et al, 2020 ). Social isolation and being away from family could be the major reasons for the same ( Upadhyay et al, 2020 ). Our study also reported a significant difference in Corona Anxiety Score when tested against gender, level of education, occupation, history of contact with COVID-19 patients, and symptom status.…”
Section: Discussionmentioning
confidence: 99%
“… 6 A recent study conducted in quarantine facility centers in India reported that depression, anxiety, and stress were found in 49.4%, 40.9%, and 75.8% of the residents, respectively. 7 …”
Section: Introductionmentioning
confidence: 99%
“…6 A recent study conducted in quarantine facility centers in India reported that depression, anxiety, and stress were found in 49.4%, 40.9%, and 75.8% of the residents, respectively. 7 Quarantine, although designed to be protective of individual and public health, brings with it negative health impacts that need to be understood, prevented, and mitigated. The more public health officials understand the nature of the quarantine experience, the more it can be designed to reduce adverse impacts, promote protective factors, and optimize short and long-term outcomes from a mental and physical well-being perspective.…”
Section: Introductionmentioning
confidence: 99%